An Extensive Research on Acoustic Underwater Wireless Sensor Networks (AUWSN) - Joby, P. P. (IRO Journal on Sustainable Wireless Systems, 2022)
It is a well-known fact that water covers nearly 71% of the total earth's surface. This makes the extraction of most valuable information from the seafloor and underwater resources extremely difficult for humans. As a result, in order to meet the requirements of underwater exploration, researchers have focused their efforts on developing new technologies for establishing underwater communication. The recent advancements in wireless acoustic underwater sensing and communication technology has resulted in an upsurge in the exploration of abundant underwater natural resources. This research study intends to provide a comprehensive overview of acoustic underwater sensor networks, including their implementation techniques, routing algorithms and applications. This study also provides a comparative analysis on various acoustic wireless sensor networks deployment in order to find the existing research gaps. Furthermore, some real-time AUWSN applications were reviewed, providing diverse and insightful information about the AUWSN approach. Finally, the study discusses about some potential future research directions for designing the next-generation AUWSNs.
Keywords: Acoustic networks; underwater communication; autonomous underwater vehicle; network analysis; underwater sensors